Feminist human–computer interaction: Struggles for past, contemporary and futuristic feminist theories in digital innovation. (April 2022) - Bellini, Rosanna; Meissner, Janis; Finnigan, Samantha Mitchell; Strohmayer, Angelika
In this short paper, we introduce our Special Section in Feminist Theory titled 'Feminist human-computer interaction: Struggles for past, contemporary and futuristic feminist theories in digital innovation'. Over the last years, we worked with the authors of the articles presented herein to bring together feminist theories with their practical application in the design, development, use and exploration of digital technologies. Our section follows three aspects: (1) an overview of past feminist histories and discourse; (2) the development of actionable, contemporary theory; and (3) speculative futures of what a feminist human-computer interaction (HCI) could be. Together with the contributing authors, we are excited to explore these areas of post-disciplinary connection at the intersection of theory, practice and activism.